SUCCESSFUL MANAGEMENT OF FALSE ANESTRUS IN A PUNGANUR COW BY DOUBLE PGF2α PROTOCOL - S. Maheswari; K. Ravikumar; R. Sureshkumar; G. Monica; J. Umamageswari; S. Sathishkumar; D. Dhanasekara Varma; V. Reshma (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A pluriparous Punganur cow calved 9 months back was presented to Large Animal Gynaecology Unit with the history of anestrus. On rectal examination, uterus was flaccid and uterine horns were similar. Transrectal ultrasonography revealed presence of corpus luteum in the right ovary and small follicles in the left ovary. Based on the history, per rectal examination and transrectal ultrasonography, the case was diagnosed as false anestrus due to silent estrus. Double prostaglandin (PGF2α) protocol was followed. After first injection of PGF2α, animal was examined on day 11 where the ultrasonography revealed corpus luteum in the right ovary and medium size follicle in the left ovary. Animal came to estrus after 72 hours of second PGF2α injection and inseminated. Pregnancy was confirmed by 90 days post insemination.